Effects of PEEP on Hemodynamic Variables in Pigs Submitted to Volume-controlled Ventilation under Pneumoperitoneum associated to Cephalodeclive - Ido, Cléber Kazuo [UNESP]; Nunes, Newton [UNESP] (Universidade Federal do Rio Grande do Sul, 2021)
Background: Videolaparoscopic procedures have gained prominence due to their low invasiveness, causing less surgical trauma and better post-surgical recovery. However, the increase in intra-abdominal pressure due to the institution of pneumoperitoneum can alter the patient's homeostasis. Therefore, volume-controlled ventilation, associated with positive end-expiratory pressure (PEEP), improves arterial oxygenation and prevents pulmonary collapse, but it can lead to important hemodynamic changes. The aim of this study was to evaluate, comparatively, the effects of positive end expiratory-pressure (PEEP) on hemodynamic variables of pigs submitted to volume-controlled ventilation, during pneumoperitoneum and maintained in head-down tilt and determine which PEEP value promotes greater stability on hemodynamic variables. Materials, Methods & Results: Twenty-four pigs were used, between 55 and 65-day-old, weighing between 15 and 25 kg, randomly divided into 3 distinct groups differentiated by positive end-expiratory pressure: PEEP 0 (volume-controlled ventilation and PEEP of 0 cmH2O), PEEP 5 (volume-controlled ventilation and PEEP of 5 cmH2O) and PEEP 10 (volume-controlled ventilation and PEEP of 10 cmH2O). Volume-controlled ventilation was adjusted to 8 mL/kg of tidal volume and a respiratory rate of 25 movements per min. Anesthesia was maintained with continuous infusion of propofol (0.2 mg/kg/min) and midazolam (1 mg/kg/h). Pneumoperitoneum was performed with carbon dioxide (CO2), keeping the intra-abdominal pressure at 15 mmHg and the animals were positioned on a 30° head-down tilt. The evaluations of hemodynamic variables started 30 min after induction of anesthesia (M0), followed by measurements at 15-min intervals (from M15 to M90), completing a total of 7 evaluations. The variables of interest were collected over 90 min and submitted to analysis of variance followed by Tukey's post-hoc test, with P < 0.05. The PEEP 10 group had higher values of CVP and mCPP, while the PEEP 5 group, mPAP and PVR were higher. The PEEP 0 group, on the other hand, had higher means of CI. Regarding the moments, there were differences in HR, SAP, DAP, MAP, CO, IC and TPR. Discussion: According to the literature, important hemodynamic effects due to pneumoperitoneum are reported, which can be caused by the pressure used in abdominal insufflation, CO2 accumulation, duration of the surgical procedure, hydration status and patient positioning. Mechanical ventilation associated with PEEP can also cause an increase in intrathoracic pressure and, therefore, reduce cardiac output. Cardiovascular changes are proportional to the PEEP used. Central venous pressure (PVC) measure the patient's preload, and intrathoracic pressure can interfere with this parameter. The peak pressure values in the PEEP 10 group were higher than the other groups, demonstrating that the increase in intrathoracic pressure results in higher PVC values. Regarding PAPm and PCPm, these variables can be influenced according to the PEEP values and the patient's position. In relation to CI, the increase in PEEP may reflect on intrathoracic pressure, resulting in greater compression of the heart, with a consequent reduction in cardiac output and cardiac index. Therefore, it is concluded that the PEEP effects of 0 cmH2O and 5 cmH2O on hemodynamics are discrete, under the proposed conditions.
Efeitos da PEEP na ventilação controlada a volume sobre parâmetros hemodinâmicos em suínos submetidos ao pneumoperitônio associado ao cefalodeclive
Keywords: Head-down tilt; Mechanical ventilation; PEEP; Swine; VCV